(untitled) (UKLO Proceedings, 2026)
Introduction: The principle of equality is a cornerstone of the rule of law and a prerequisite for safeguarding human rights. This research investigates the extent to which the legal order of the Republic of North Macedonia aligns with international standards on equality and non-discrimination. Methods: A mixed methodological approach was applied, combining normative-legal analysis, comparative-legal method, and doctrinal interpretation. The analysis covered key international legal instruments (Universal Declaration of Human Rights, CEDAW, European Convention on Human Rights, Istanbul Convention) in correlation with national legal acts (Constitution of the Republic of North Macedonia, Law on Prevention and Protection against Discrimination, Law on Equal Opportunities for Women and Men) during the period 2010–2023. Results: The normative-legal analysis indicates a high level of formal harmonization between national legislation and international equality standards. However, the empirical evaluation highlights a considerable implementation gap. Despite the sophistication of the de jure framework, practical enforcement remains limited due to systemic shortcomings. Discussion: The study reveals a paradox between normative compliance and practical effectiveness. Structural constraints within the judiciary, insufficient institutional resources, lack of systematic monitoring, and inconsistent application of international obligations undermine effective protection against discrimination. Bridging this gap requires transforming formal commitments into operational mechanisms to ensure genuine compliance with international equality standards and substantive human rights protection.